EFEKTIFITAS PEMANFAATAN WHATSAPP MESSENGER DENGAN KEPATUHAN KUNJUNGAN ULANG AKSEPTOR KB SUNTIK 3 BULAN PADA ERA NEW NORMAL DI KLINIK PRATAMA KASIH BUNDA DELI SERDANG - Risda Mariana Manik; Ria Oktaviance Simorangkir (Jurnal Ilmiah Kesehatan, 2024)
Purpose: To find out the effectiveness of the use of whatsapp messenger with compliance with the schedule of repeat visits for 3-month injection family planning acceptors in the new normal era. Methods: The research design used a Quasi Experiment with a two group design Pre and Post Test Control Design. Held in September-December 2020 at the Pratama Kasih Bunda Clinic, Deli Serdang. The population is all mothers of 3-month injections in the registration book of the Pratama Kasih Bunda Clinic, namely 56 people. Samples were taken using probability sampling technique with simple random sampling in order to obtain a total of 31 people in the experimental group and 25 in the control group. Results: The majority in the experimental group of 3-month injection family planning acceptors had moderate adherence (58.1%) to the schedule for repeat visits and in the control group the majority of 3-month injection family planning acceptors did not adhere (52%) to the 3-month injection family planning visit schedule. Conclusion: Based on the Mann Whiteney test, the results were p = 0.007, meaning that statistically the use of whatsapp messenger was effective for compliance with the 3-month injection family planning acceptor visit schedule in the new normal era.